THE STUDY CORRELATION BETWEEN ARM MUSCLE EXPLOSIVE POWER, CORE STABILITY STRENGTH AND ACHIEVEMENT MOTIVATION WITH THE SPEED OF 60 METERS RUN - FAHMY FACHREZZY (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this research is to obtain information on the correlation of arm muscle explosive power, core stability strength and achievement motivation with running speed of 60 meters run. This research was conducted at college in Sport Science Faculty State University of Jakarta in April 2013. Total population 80 people, the sample is taken with purposive sampling technique. The sample of the research is 35 male students. The results of the research concluded: (1). Correlation between arm muscle explosive power with speed to run 60 meters at 0.699, (2). Correlation between core stability strength with speed to run 60 meters at 0.769, (3). The correlation between achievement motivation with the running speed of 60 meters at 0.652, (4). Correlation between arm muscle explosive power, core stability strength and running speed achievement motivation with 60 meters of 0.842.